Pola Konsumsi Daging Ayam Broiler pada Rumah Tangga di Perumahan Bereng Kalingu I di Kelurahan Kereng Bangkirai Kota Palangka Raya - Herlinae Herlinae; Yemima Yemima (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2014)
The study aims to determine the pattern of broiler meat consumption and to know the effect of education, income, and number of family members on broiler meat consumption patterns of households in Bereng Kalingu I Kereng Bangkirai village, Palangka Raya. This descriptive study was to survey, interview by distributing questionnaires. Results of the 50 respondents there were 19 respondents educated diploma/bachelor, 33 low income respondents between Rp 1,000,000 - 2,000,000, 25 respondents had 2 - 3 family members. Variable of education, income, and number of family members do not affect on consumption pattern of broiler meat.